Narasi Ujaran Kebencian dalam Pemilihan Umum Kepala Daerah (PILKADA) - Musyafak, Najahan; Ulama'i, Ahmad Hasan Asy'ari (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2019)
Hate speech on social media has become a theme of discussion in various forms of discourse in society. This paper focuses on expressions of hate speech related to regional political election uploaded through posts from personal and group accounts on the Facebook social media platform from January to July 2018. This study uses content analysis by adopting Soesilo's six hate speech criteria. The results of the study showed that the forms of hate speech on Facebook were expressed in the form of photos, drawings, illustrations, memes, and words that had the connotation of provocation, insults, and incitement. Hate speech comes from personal and group accounts, addressed to individuals, public officials such as presidents, party leaders, and the government.Ujaran kebencian di media sosial telah menjadi tema pembahasan dalam berbagai bentuk wacana di masyarakat. Tulisan ini fokus pada ekspresi ujaran kebencian yang terkait dengan masalah Pemilihan Kepala Daerah yang diunggah melalui postingan dari akun personal maupun kelompok dalam platform media sosial facebook selama Januari sampai bulan Juli 2018. Studi ini menggunakan analisis isi dengan mengadopsi enam kriteria ujaran kebencian Soesilo. Hasil studi menunjukkan bahwa bentuk ujaran kebencian di facebook diungkapkan dalam bentuk foto, gambar, ilustrasi, meme, dan kata-kata yang memiliki konotasi provokasi, penghinaan, dan hasutan. Ujaran kebencian bersumber dari akun pribadi dan kelompok, ditujukan kepada individu, pejabat publik seperti presiden, ketua partai, dan pemerintah.